2016
DOI: 10.1155/2016/9270691
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Content and Pharma‐Nutrition Study on Eleutherococcus senticosus Fruits Intractum

Abstract: In the past two decades public interest in herbal products has increased significantly in Europe, especially in the plant-based products from non-European traditions. Eleutherococcus senticosus has been used for the treatment of inflammatory diseases, anemia, and rheumatoid arthritis. The Eleutherococcus senticosus fruits intractum was examined for the content of phenolic acids (LC-ESI-MS/MS), minerals (AAS), TPC, and TFC (spectrophotometric assay). The antioxidant activity was determined using free radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In Załuski et al's previous studies, aescin was used as the standard compound. The 30.1% level of inhibition was obtained for the concentration of 100 μ g [ 12 ]. It should be noticed that the extract possesses chemical structures that may be used as possible inhibitors of Hyal, showing a stronger potency than aescin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Załuski et al's previous studies, aescin was used as the standard compound. The 30.1% level of inhibition was obtained for the concentration of 100 μ g [ 12 ]. It should be noticed that the extract possesses chemical structures that may be used as possible inhibitors of Hyal, showing a stronger potency than aescin.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acid profile was determined according to the modified methods of Nowacka et al, [ 19 ], Pietrzak et al, [ 20 ], and Załuski et al, [ 12 ]. In this case, the Agilent 1200 Series HPLC system (Agilent Technologies, USA) connected to a 3200 QTRAP MS/MS (AB Sciex, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that Siberian ginseng is an effective scavenger of peroxynitrite (ONOO − ), while to a Siberian ginseng MeOH extract was found the maximum ferric reducing antioxidant power (FRAP) . Also, it has been utilized in the treatment of anaemia, inflammatory disorders and rheumatoid arthritis .…”
Section: Major Medicinal Plants Used In Medication System As Anti‐agementioning
confidence: 99%
“…With regard to its pharmacological aspects, E. sessiliflorus has been used in traditional medical protocols as a tonic, analgesic, antihypertensive, and antidiabetic agent. Załuski's previous studies have shown that the fruits may reduce DPPH ∗ radical, inhibit lipid peroxidation, and have an ion-chelating ability [ 6 10 ]. In food industry, only species native to Asia are used, while species cultivated in Europe are not yet used commercially.…”
Section: Introductionmentioning
confidence: 99%